Once upon a tower - James, Eloisa (Avon romance., 2013)
"As an extremely wealthy laird, Gowan Stoughton, Duke of Kinross, can have any of the maidens at the ball he attends. The only problem is they are all English and Gowan is not so certain they are suitable. He is accustomed to the hard-working lasses from his Highlands, not these dainty noblewomen who spend their days drinking tea or some other such nonsense. But then he makes the acquaintance of Lady Edith Gilchrist. Utterly bewitched by the emerald-eyed beauty with lush golden locks, he knows he must have her. He must free her from her tower. 'Edie' had the misfortune of being dreadfully ill at her debut ball and barely remembers what Gowan looks like. Even worse, she accepted his proposal the following day. Edie's only true passion is playing music--until Gowan writes a scandalous letter and stirs the most irresistible desire. Yet when they marry, Edie realizes her husband needs a lesson and locks herself in a tower. Somehow Gowan must find a way to enter the tower and convince his new bride that she belongs in his arms."--P. [4] of cover.